Analisis Pengaruh Konsumsi, Investasi, Dan Belanja Pemerintah Terhadap PDB Di Indonesia: Pendekatan Data Time Series Tahun 1995-2024 - Wijayati, Dilla; Sawitri, Novita Della; Fajarani, Annisah Aulia (Indo Publishing, 2025)
This study aims to empirically examine the effect of consumption, investment, and government expenditure on Indonesia’s Gross Domestic Product (GDP) using time series data from 1995 to 2024. The research employs a quantitative approach with multiple linear regression analysis based on secondary data obtained from the World Bank. Classical assumption tests are conducted to ensure the validity of the econometric model. The results indicate that consumption and government expenditure have a positive effect on GDP, while investment does not show a statistically significant effect in the partial test. However, the simultaneous test reveals that consumption, investment, and government expenditure jointly have a significant impact on Indonesia’s GDP. The coefficient of determination shows that a large proportion of GDP variation can be explained by the variables included in the model. These findings suggest that household consumption and effective government spending play a crucial role in supporting economic growth, while the contribution of investment depends on structural and efficiency factors. The study provides important policy implications for strengthening fiscal effectiveness and promoting sustainable economic growth in Indonesia